Improving Instructional Delivery Using Blended Learning in College of Education: Lecturers’ Perspective - Agim, Mary Alorye; Igwe, Kingsley Ogazi; Olannye, Veronica Ekwi (Digital Technologies Research and Applications, 2025)
The paper ascertained the perspective of lecturers in improving instructional delivery using blended learning in College of Education in South‑South and South East Nigeria. Two specific purposes guided the study. They were further developed into two research questions and two hypotheses. The paper adopted a descriptive survey design. The population of the study comprised 425 business education lecturers in College of Education, in South‑South and South East Nigeria. The entire population of 425 lecturers was used as a sample for this study. The instrument for data collection was questionnaire and interview schedules. The instrument was validated and tested for internal consistency using Cronbach Alpha reliability coefficient. The coefficient obtained was 0.83. Out of 425 copies of the questionnaire administered, only 321 representing 93% was retrieved and used for data analysis. Mean and standard deviation was used to answer the research questions and t‑ test statistic to test the hypotheses at 0.05 level of significance. Results indicate that training of personnel and provision of facilities are necessary in using blended learning to improve instructional delivery. Also, gender was not significant in the perception of lecturers in both training needs and provision of facilities to improve instructional delivery using blended learning. It was concluded that effective training and provision of the right facilities to support blended learning will help to improve instructional delivery in tertiary institutions. It was recommended that adequate training should be given to educators to enable them to use blended learning in improving teaching and learning.